ESTIMASI BIAYA REMEDIASI EKOSISTEM MANGROVE TERCEMAR HIDROKARBON: STUDI KASUS TAHURA NGURAH RAI, TELUK BENOA - Wayan Hari Premananda (Nusantara Hasana Journal, 2026)
The mangrove ecosystem within the Ngurah Rai Grand Forest Park (Tahura) in Benoa Bay experienced vegetation dieback and degradation across an area of 3,800 m², triggered in part by hydrocarbon contamination resulting from a fuel oil (biosolar) seepage from a pipeline near the Bali Mandara Toll Road exit. This study aims to determine the quantity and volume of recovery requirements based on the condition of the affected area, develop a cost estimate for each stage of mangrove ecosystem recovery by applying the remediation cost concept—defined as the cost required to restore contaminated environmental conditions to an established standard—and analyze the cost component that contributes most significantly to the total recovery cost. A descriptive quantitative approach was used, decomposing recovery activities into five cost component groups: preparation and supporting facilities, soil and land handling, bioremediation, revegetation–maintenance–monitoring, and temporary storage site (TPS) operations. The recovery area was set at 3,800 m² based on measurements by the National Land Agency, with an assumed excavation depth of 0.8 m, yielding an affected material volume of 3,040 m³. The results indicate a total estimated recovery cost of IDR 23,158,025,000, with preparation and supporting facilities—particularly the acquisition of an 800 m² TPS site—identified as the largest cost contributor. These findings suggest that decisions regarding TPS location and land ownership status significantly influence total recovery costs, and should therefore be a primary consideration in budget planning for the recovery of hydrocarbon-contaminated coastal ecosystems.